(3GdJUQjM HGdePgH GdUMjMs - (3fhQ GdOjf CHh YHO Gddg MejOGf Hf jMji Hf MejOGf GdbGSejs
(3ChdgG (B:s
(3CMeO Gddg JYGdi MeO eYJQa HhMOGfjJg hLdGdg hYOdg hMceJg SHMGfg ai LejY CaYGdg hCbhGdg s
(3BNQgG (B:s
(3hdCLd chf cKjQ ef GdCSeGA ehVhYkG Ydi ZjQ eSei , Je Pdc hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJGQjNs